The solution for the given equations x + 3y = 5 and x - 3y = -1 are x=2 and y=1.
Step-by-step explanation:
The given is,
......................................(1)
....................................(2)
Step:1
By elimination method,
Subtracting Equations (1) and (2),
( - )
( ) + ( ) = ( )
= 6
= 1
Step:2
Substitute the value of y in equation (1),
+ ( 3 × 1 ) = 5
= 5-3
= 2
Step:3
Check for Solution,
Substitute the values of x and y in Eqn (1),
2 + ( 3 × 1 ) = 5
5 = 5
Result:
The solution for the given equations x + 3y = 5 and x - 3y = -1 are x=2 and y=1, by elimination method.